Benzylethyldimethylammonium bromide - Hodorowicz, Maciej (International Union of Crystallography, 2008)
The crystal structure of the title compound, C(11)H(18)N(+)·Br(−), has been determined as part of an ongoing study of the influence of the alkyl chain length on amphiphilic activity of quaternary ammonium salts. The title salt forms a three-dimensional network of ionic contacts through weak C—H⋯Br hydrogen bonds, with donor–acceptor distances in the range 3.757 (2)–3.959 (2) Å, in which methyl groups serve as donors.